2006
DOI: 10.1080/03602550600887368
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Iron Powder Filled Polystyrene Composites

Abstract: This article reports on an experimental study of the physical and mechanical properties of Polystyrene (PS) and Fe-PS polymer composites containing 5, 10, and 15 vol.% of Fe powder. After mixing Fe powder and PS in a twin-screw extruder, an injection-molding machine was used to prepare unfilled PS and Fe-PS polymer composite samples. After that, the material properties were experimentally determined for each sample. The investigated material properties included the modulus of elasticity, yield and tensile stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Costa et al 14 reported that the large difference between conductivities of iron particles and PS promotes defect charges in the interfaces, which are loosely bound and are responsible for the electrical conductivity behavior at lower concentrations. Taşdemir and Gulsoy 15 reported that the physical properties are affected by adding the iron particles to the PS matrix. Recently, Elimat et al 16 studied the effect of iron particle sizes on the thermal conductivity of PS composites and found large enhancement in the thermal conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Costa et al 14 reported that the large difference between conductivities of iron particles and PS promotes defect charges in the interfaces, which are loosely bound and are responsible for the electrical conductivity behavior at lower concentrations. Taşdemir and Gulsoy 15 reported that the physical properties are affected by adding the iron particles to the PS matrix. Recently, Elimat et al 16 studied the effect of iron particle sizes on the thermal conductivity of PS composites and found large enhancement in the thermal conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Yani artan konsantrasyon ile birlikte malzemenin erime entalpisi artmış böylelikle bozunma entalpisi yükselmiştir. Çalışmamıza benzer şekilde Gülsoy ve Taşdemir (Gülsoy ve Taşdemir, 2006); polipropilen matris içerisine demir tozu ilavesiyle kompozitlerin fiziksel özelliklerini incelediği çalışmasında artan demir miktarı ile HDT ve vicat sıcaklıklarının arttığını gözlemlemiştir. Şekil 4C'de verilen nem testi sonuçları incelendiğinde; tufal ilavesiyle nem oranını azaldığı dolayısıyla neme karşı direnç kazandığı görülmektedir.…”
Section: Bulgular Ve Tartişmaunclassified